Konversi Gondorukem menjadi Fine Chemicals melalui Reaksi Hydrocracking Menggunakan Katalis Ni-Mo/Î³-Al2O3 - Jayanti, Yeni Fitriana; Savitri, Savitri; Rinaldi, Nino; Priatmoko, Sigit; Jumaeri, Jumaeri (Indonesian Journal of Chemical Science, 2017)
A preliminary study of the conversion of rosin oil to fine chemicals through hydrocracking reactions using Ni-Mo/Î³-Al2O3 catalysts has been studied. The purpose of this study was to determine the effect of temperature, initial pressure of hydrogen gas, and reaction time to the reaction of hydrocracking of rosin oil to produce fine chemicals. Hydrocracking of rosin oil is performed on a batch autoclave reactor by varying the reaction temperature (300-350 Â°C), hydrogen gas pressure (10-40 bar), and reaction time (60-240 min). The amount of Ni-Mo/Î³-Al2O3 catalyst used is 1% w/w of rosin oil. The results showed that the compounds contained in rosin oil experienced hydrocracking reaction with the use of high reaction temperature. The use of low hydrogen gas pressure is able to split of rosin oil into fine chemicals, whereas the long reaction time results in the rosin oil being crushed producing more products. The hydrocracking reaction of rosin oil using Ni-Mo/Î³-Al2O3 catalyst produces the optimum product if high temperatures used with low hydrogen gas usage and reaction time are used relatively long.